2001
DOI: 10.1302/0301-620x.83b7.11827
|View full text |Cite
|
Sign up to set email alerts
|

Medial unicompartmental arthroplasty after failed high tibial osteotomy

Abstract: Satisfactory selection criteria are essential for the successful outcome of unicompartmental knee arthroplasty (UCA). We report the frequency of revision of the Oxford medial unicompartmental arthroplasty in knees previously treated for anteromedial osteoarthritis by high tibial osteotomy (HTO). The combined results from three sources were used to allow statistical analysis of this uncommon subgroup. In the combined series of 631 knees (507 patients) which had medial unicompartmental replacement, 613 were prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 10 publications
0
15
0
2
Order By: Relevance
“…Although Kozinn and Scott recommend a total knee prosthesis when subchondral bone is exposed, Goodfellow et al state that correction of the malalignment relieves the patella from the increased load [15,21]. Rees already demonstrated that a high tibial osteotomy is a contraindication to a medial OUKP [28]. This is supported by our poor results in this specific subgroup.…”
Section: Discussionmentioning
confidence: 59%
“…Although Kozinn and Scott recommend a total knee prosthesis when subchondral bone is exposed, Goodfellow et al state that correction of the malalignment relieves the patella from the increased load [15,21]. Rees already demonstrated that a high tibial osteotomy is a contraindication to a medial OUKP [28]. This is supported by our poor results in this specific subgroup.…”
Section: Discussionmentioning
confidence: 59%
“…Vorlat et al [50] did not show successful outcome of UKAs after HTO. Likewise, the revision rate after HTO was 28% in Rees’ series [40] after a FU period of 2.9 years. One patient with a previous HTO in this series was revised from UKA to TKA.…”
Section: Discussionmentioning
confidence: 99%
“…However, high failure rates of UKA conversion from HTO have been reported18 because of technical problems associated with ligamentous instability, or lateral wear and subsequent failure. Therefore, we selected a joint preserving surgery as the initial treatment.…”
Section: Discussionmentioning
confidence: 99%